Br-COFs material and preparation method thereof, and preparation method of lithium metal battery covalent organic framework material interfacial film
By using covalent organic frame material Br-COFs as artificial interface mask in lithium metal batteries, the problem of lithium dendrites and the difficulty of interface mask control are solved, and the high cycle stability and battery performance improvement of lithium metal batteries are achieved.
Patent Information
- Application Number
- CN202411403139.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-10-09
AI Technical Summary
The negative electrode materials of existing lithium metal batteries have problems with lithium dendrites, which leads to low energy density and poor stability of the battery, and it is difficult to accurately control the thickness and component distribution of the artificial solid electrolyte interface film.
Using the covalent organic frame material Br-COFs, spherical COFs are synthesized by reacting 1,3,5-tris(4-aminophenyl)benzene and 2,5-dibromobenzene-1,4-diformaldehyde in an organic solvent. , a stable and uniform artificial interface mask was formed in combination with a PVdF adhesive, and applied to the copper electrode by a conventional coating method.
The cycle stability of lithium metal batteries is improved, and the cycle can be stable for more than 200 hours without chemical reaction with lithium metal and organic electrolyte components, which improves the power performance of the battery.
Smart Images

Figure CN119241789A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation of artificial interface membranes for lithium metal batteries, and specifically relates to a preparation method of a covalent organic framework material and application in lithium metal battery interface membranes. Background Art
[0002] With the rapid development of artificial intelligence technology and electronic devices, as well as the scarcity of fossil resources and the arrival of the energy crisis, the vigorous development of new energy can alleviate the energy crisis and meet the energy needs of all walks of life. At the same time, energy storage devices must also accelerate their development to obtain better energy storage properties. Since its commercialization in the 1990s, lithium-ion batteries have long dominated the energy storage field with their high safety, long cycle life, environmental friendliness, and high energy density. Today, the hot Xiaomi, BYD and Tesla new energy vehicles all use lithium-ion batteries. The negative electrode materials of lithium-ion batteries are mainly graphite (~372mAh / g), lithium titanate (~175mAh / g), metallic lithium (~3860mAh / g), silicon-based alloys (~2500mAh / g), metallic lithium (~3860mAh / g), and tin-based alloys (~850mAh / g). Graphite materials are easy to prepare, have good stability, and are cheap, but have low specific capacity. Lithium titanate materials can discharge at high power and have good stability, but their specific capacity is also relatively low. Although silicon-based alloys have a high specific capacity, the material is prone to volume expansion. Metallic lithium has the highest specific capacity, but the growth of lithium dendrites can cause some safety issues. Tin-based alloys have a high specific capacity but poor stability. In summary, although the negative electrode materials of lithium-ion batteries all have certain disadvantages, the specific capacity of lithium metal electrodes is as high as ~3860mAh / g. If the problem of lithium dendrite growth can be solved, then lithium metal electrodes can greatly improve the energy density of batteries.
[0003] Lithium metal batteries are similar to lithium ion batteries, both using carbonates, ethers, ionic liquids and other solvents as electrolyte solvents. From the development history of lithium metal batteries and the current research status, most of the research focuses on obtaining excellent solid electrolyte interface (SEI) through the regulation of electrolyte components and solvation structure. The excellent solid electrolyte interface obtained through electrolyte design can also inhibit the growth of lithium dendrites, allowing stable deposition / stripping of lithium-lithium symmetric batteries. However, it is difficult for us to accurately control the thickness and component distribution of the interfacial film produced by the decomposition of the electrolyte. In order to promote the development of artificial SEI membranes and achieve the goal of accurately controlling the thickness, components, and physical / chemical properties of SEI, there are currently some reports on the synthesis of artificial SEI. For example, Xiulin Fan's team synthesized a polyimide covalent organic framework (COFs) material and used it as an artificial SEI membrane for lithium metal batteries. After coating with COFs material, the coulombic efficiency of lithium-copper batteries remained above 99% after 400 cycles [Wu X, Zhang S, Xu X, Wen F, Wang H, Chen H, Fan X, Huang N. Lithiophilic Covalent Organic Framework as Anode Coating for High-Performance Lithium Metal Batteries. Angew Chem Int Ed Engl. 2024, 63, e202319355]. Shanlin Qiao's team prepared a highly crystalline spherical COFs material and used it as a lithium metal electrode SEI film. The lithium metal electrode coated with this material can make lithium ions deposited uniformly and densely, and the lithium-lithium symmetric battery can be operated at 4 mA / cm 2 After cycling for 2400 hours at a current density of 1.5 %, the overpotential hardly increases [Wenbo Wang, Zehua Yang, Yantao Zhang, Aiping Wang, Yunrui Zhang, Liling Chen, Qing Li, Shanlin Qiao, Highly stable lithium metal anode enabled by lithiophilic and spatially-confined spherical-covalent organic framework, Energy Storage Materials, 2022, 46, 374-383]. Xunhui Xiong's team synthesized a dynamic gel containing reversible imine groups, which can be used as an artificial SEI film protective layer on the surface of lithium metal. The lithium-lithium symmetric battery cycled by the lithium metal electrode treated with the gel can be operated at 6 mA / cm2 Stable cycle for 3000 hours at low current density [Dynamic gel as artificial interphase layer for ultrahigh-rate and large-capacity lithium metal anode, Chen C, Zhang J, Hu B, Liang Q, Xiong X. Dynamic gel as artificial interphase layer for ultrahigh-rate and large-capacity lithium metal anode. Nat Commun. 2023, 14, 4018].
[0004] The preparation methods of COFs materials or other functional materials mainly include chemical vapor deposition (CVD), solvent thermal synthesis, mechanical synthesis, microwave synthesis, ion thermal synthesis and hydrothermal synthesis.
[0005] The COFs material in this work is synthesized by dissolving 2,5-dibromobenzene-1,4-dicarboxaldehyde and 1,3,5-tri(4-aminophenyl)benzene in an organic solvent and continuously stirring and reacting. The synthesized COFs material and the adhesive PVdF are dissolved in N-methylpyrrolidone (NMP) at a certain mass ratio to prepare a slurry. Subsequently, the above slurry is coated on the surface of copper foil as an artificial solid electrolyte interface membrane for lithium metal batteries through a traditional battery material coating method. The copper electrode sheet prepared with the COFs material will be used in the electrochemical performance test of lithium metal batteries. Compared with traditional solid electrolyte interface membranes, the materials and artificial interface membranes prepared by this method are more stable and uniform. Summary of the invention
[0006] The purpose of the present invention is to prepare a covalent organic framework material that can be stably used as an artificial interface membrane for lithium metal batteries. The material is spherical, uniform, and orderly in structure, does not chemically react with lithium metal and organic electrolyte components, is heat-resistant and corrosion-resistant, and a copper electrode coated with Br-COFs material and a lithium metal electrode assembled into a half-cell can be stably cycled for more than 200 hours in an electrolyte, and the cycle stability is better than that of ordinary lithium / copper batteries.
[0007] The present invention is achieved through the following technical solutions.
[0008] The present invention provides a method for preparing a covalent organic framework material for an artificial interface membrane of a lithium metal battery. A simple preparation method is adopted to obtain a spherical COFs material of uniform size, which is coated on a copper electrode to form a stable and uniform artificial interface membrane.
[0009] A method for preparing a covalent organic framework material comprises the following steps:
[0010] 1,3,5-tri(4-aminophenyl)benzene (TAPB) and 2,5-dibromobenzene-1,4-dicarboxaldehyde (BBDD) are dissolved in an organic solvent, and acetic acid is added dropwise to the above solution. The reaction mixture is stirred continuously at a suitable temperature for a required time. After the reaction is completed, Br-COFs are obtained by filtering, washing, centrifuging and drying.
[0011] Preferably, the specific steps of synthesizing Br-COF are: mixing 1,3,5-tris(4-aminophenyl)benzene and 2,5-dibromobenzene-1,4-dicarbaldehyde with an organic solvent in a flat-bottom flask, magnetically stirring for 10 to 20 minutes, then adding acetic acid to the flask, vigorously stirring the resulting mixture at 25 to 40° C. for 20 to 26 hours, then filtering the reaction solution, washing, and centrifuging and drying to obtain Br-COFs.
[0012] Preferably, the organic solvent is one of acetonitrile, acetone and N,N-dimethylformamide.
[0013] Preferably, the acetic acid concentration is 16 mol / L to 18 mol / L.
[0014] Preferably, the reaction temperature is 25-40° C. and the reaction time is 20-26 hours.
[0015] Preferably, the organic solvent is one of acetonitrile, acetone and N,N-dimethylformamide.
[0016] Preferably, the washing is centrifugal washing with acetonitrile, acetone and anhydrous ethanol in sequence for 2 to 3 times.
[0017] Preferably, the drying is vacuum drying, the drying temperature is 100 to 150° C., and the drying time is 6 to 24 hours.
[0018] The Br-COFs material prepared by the above method is spherical with uniform size, a diameter of 960 nm and a pore size of 3.15 nm.
[0019] Furthermore, the prepared Br-COFs material and PVdF adhesive are mixed and dispersed in an organic solvent in a certain proportion to obtain a uniformly dispersed slurry, which is then coated on the surface of the copper foil in a certain thickness according to a traditional coating method to obtain a Cu electrode covered with a Br-COFs film.
[0020] Preferably, the ratio of the Br-COFs material to the PVdF adhesive is 8.5:1.5 to 9.5:0.5.
[0021] Preferably, the coating thickness of the Br-COFs interface film is 55 microns to 15 microns.
[0022] Preferably, the organic solvent used to disperse the Br-COFs material and the PVdF adhesive is one of N-methylpyrrolidone, dimethyl sulfoxide and N,N-dimethylformamide.
[0023] The Br-COFs material prepared by the present invention is uniform and orderly, with a size of about 0.9-1 micron. It is coated on the surface of a copper electrode in a certain thickness as an artificial interface membrane for a lithium metal battery. Compared with a traditional solid electrolyte interface membrane, the interface membrane can enable a lithium / copper battery to stably cycle for more than 200 hours. The Br-COFs material has great application potential in the field of artificial interface membranes for lithium metal batteries.
[0024] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0025] (1) The present invention proposes for the first time to use Br-COFs material as an artificial interface membrane for lithium metal batteries. The Br-COFs material is a spherical particle of 0.9-1 micrometers, rich in Br groups in structure, with a pore size of 3.15 nm, which is mesoporous and is conducive to the diffusion and migration of lithium ions at the interface, thereby improving the battery power performance.
[0026] (2) The Br-COFs material prepared by the present invention as an artificial interface membrane of a lithium metal battery does not chemically react with organic electrolyte components and lithium metal electrodes, and can improve the cycle stability of lithium metal batteries compared with traditional solid electrolyte interface membranes. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The synthetic route of the Br-COFs material prepared in Example 1 of the present invention and the molecular structure diagram of the corresponding reactants and products.
[0028] Figure 2 The scanning electron microscope image and particle size distribution diagram of the Br-COFs material prepared in Example 1 of the present invention.
[0029] Figure 3 It is the infrared characterization image of the Br-COFs material prepared in Example 1 of the present invention and the infrared spectrum of the reactants TAPB and BBDD obtained after theoretical calculation optimization.
[0030] Figure 4 The nitrogen adsorption-desorption curve and pore size distribution curve of the Br-COFs material prepared in Example 1 of the present invention are shown.
[0031] Figure 5 This is the X-ray diffraction pattern of the Br-COFs material prepared in Example 1 of the present invention.
[0032] Figure 6 This is a comparison chart of the time-voltage performance of the lithium-copper battery of Example 3 of the present invention and Comparative Example 1. DETAILED DESCRIPTION
[0033] The specific implementation of the present invention is further described in detail below in conjunction with the drawings and embodiments, but the implementation of the present invention is not limited thereto.
[0034] Example 1
[0035] The preparation of Br-COFs material includes the following steps:
[0036] First, 30 mg of 1,3,5-tris(4-aminophenyl)benzene (TAPB) and 30 mg of 2,5-dibromobenzene-1,4-dicarbaldehyde (BBDD) were added to a flask containing 30 mL of acetonitrile. The mixture was then stirred at room temperature while 1.6 mL of
[0037] 17.5 mol / L acetic acid. After stirring for 12 hours, the reaction product was filtered and washed with acetonitrile and acetone in sequence. Finally, Br-COFs powder was obtained after vacuum drying at 120°C overnight.
[0038] Example 2
[0039] The preparation of the artificial interface membrane of Br-COFs material includes the following steps:
[0040] The Br-COFs material and the PVdF adhesive were dissolved in 1-2 mL of N-methylpyrrolidone solvent at a mass ratio of 9:1 (0.09 g Br-COFs: 0.01 g PVdF) to obtain a mixed slurry. The slurry was rotated and dispersed using a degassing machine to obtain a uniformly distributed slurry. The obtained slurry was coated on the surface of the copper foil at a certain thickness using an automatic coating machine to obtain a coated Br-COFs-Cu electrode. The Br-COFs-Cu electrode was transferred to a 120°C vacuum oven to evaporate the N-methylpyrrolidone solvent in the electrode.
[0041] Example 3
[0042] The Br-COFs-Cu electrode obtained in step (1) of Example 2 was assembled with a lithium metal electrode into a Br-COFs-Cu / Li button half-cell and its electrochemical performance was tested.
[0043] Comparative Example 1
[0044] Using the same electrolyte as in Example 3, a lithium metal electrode and a common copper electrode were assembled into a Cu / Li button half-cell and its electrochemical performance was tested.
[0045] Figure 2SEM characterizes the morphology of Br-COFs materials. It can be seen from the figure that Br-COFs materials are spherical and uniform in size. The particle size distribution diagram shows that most of the particle sizes are distributed around 960nm.
[0046] Figure 3 Br-COFs materials were subjected to infrared testing to characterize their structure and composition. -1 ~1660cm -1 The -C=N peak appeared, indicating that the amine group of the reactant TAPB and the aldehyde group of BBDD underwent a Schiff base cross-linking reaction. Only weak -CHO and -NH2 peaks were detected in the product. In addition, the stretching vibration peak of -C-Br was detected at 800-1060 in the Br-COFs material, further indicating that BBDD was involved in the reaction.
[0047] Figure 4 This is the specific surface adsorption and pore size distribution diagram of Br-COFs material. It can be seen from the figure that the pore size of Br-COFs material is about 3.15nm.
[0048] Figure 5 X-ray diffraction pattern of Br-COFs material. The broad XRD diffraction peak of Br-COFs indicates that the material is not necessarily single crystal and has weak crystallinity.
[0049] Figure 6 The electrochemical test performance evaluation results of the Br-COFs-Cu / Li battery in Example 3 of the present invention and the Cu / Li in Comparative Example 1 are shown. It can be seen that the Br-COFs-Cu / Li battery has excellent cycle stability performance, and the battery can be stably cycled for more than 200 hours, while the battery polarization of the Cu / Li battery increases significantly after 150 hours of cycling, indicating that the cycle stability and interface impedance of the system are large. The performance of the Br-COFs-Cu electrode is significantly better than that of the ordinary Cu electrode, indicating that the Br-COFs material is conducive to the standardized deposition of lithium ions and the stability of the electrode interface.
[0050] It should be understood that the above detailed description of the technical solution of the present invention with the help of optimized embodiments is illustrative rather than restrictive, and it cannot be determined that the specific implementation methods of the present invention are limited to this. For ordinary technicians in the technical field to which the present invention belongs, without departing from the concept of the present invention, modifications to the technical solutions recorded in the embodiments, or equivalent replacement of some of the technical features therein, should be deemed to fall within the scope of patent protection determined by the claims submitted for the present invention.
[0051] The above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing a Br-COFs material, characterized in that: The steps include: 1,3,5-tri(4-aminophenyl)benzene and 2,5-dibromobenzene-1,4-dicarboxaldehyde are dissolved in an organic solvent, and then acetic acid is added dropwise to allow the reaction mixture to react under stirring conditions. After the reaction is completed, Br-COFs are obtained by filtering, washing, centrifuging and drying.
2. The preparation method according to claim 1, characterized in that: The organic solvent is one of acetonitrile, acetone and N,N-dimethylformamide.
3. The preparation method according to claim 1, characterized in that: The acetic acid concentration is 16 mol / L to 18 mol / L.
4. The preparation method according to claim 1, characterized in that: The reaction temperature is 25-40°C.
5. The preparation method according to claim 1, characterized in that: The reaction time is 20 to 26 hours.
6. The preparation method according to claim 1, characterized in that: The washing is performed by centrifugation washing with acetonitrile, acetone and anhydrous ethanol in sequence for 2 to 3 times.
7. A Br-COFs material obtained by the preparation method according to any one of claims 1 to 6, characterized in that: The Br-COF material is spherical with uniform size, a diameter of 960 nm, a pore size of 3.15 nm, and is rich in Br groups in structure.
8. A lithium metal battery interface film prepared from the Br-COFs material according to claim 7, characterized in that: The Br-COFs material and the PVdF adhesive are dissolved in an organic solvent to obtain a uniformly dispersed Br-COFs slurry, and then the Br-COFs slurry is coated on the surface of a copper foil to obtain a Cu electrode covered with a Br-COFs film.
9. The method for preparing the Br-COFs interface film according to claim 8, characterized in that: The ratio of Br-COFs material to PVdF adhesive is 8.5:1.5-9.5:0.5; the organic solvent used to dissolve / disperse the material is one of N-methylpyrrolidone, dimethyl sulfoxide, and N,N-dimethylformamide.
10. The method for preparing the Br-COFs interface film according to claim 8, characterized in that: The coating thickness of the slurry on the copper foil is 5 microns to 15 microns.
Citation Information
Patent Citations
Application of covalent organic framework material in lithium metal negative electrode protection
CN112993256A
Ionic covalent organic framework material, preparation method and application thereof, and lithium metal negative electrode material
CN114213670A
Quickly synthesized COFs (Covalent Organic Frameworks) material and application thereof to detection of water content in organic solvent
CN116023608A
NH2-COFs (at) ZnS photocatalytic material as well as preparation method and application thereof
CN117143305A
Cited By
Method for regulating and controlling functionalization of lithium battery diaphragm COFs based on catalyst concentration
CN120879142A
A method for functionalizing lithium battery separators based on COFs by regulating catalyst concentration
CN120879142B
Method for flattening lithium battery diaphragm at two-phase interface and application in preparation of COFs diaphragm
CN120879143A
